Plasma thyroid hormone concentration is associated with hepatic triglyceride content in patients with type 2 diabetes. Issue 1 (January 2016) - Bril, Fernando; Kadiyala, Sushma; Portillo Sanchez, Paola; Sunny, Nishanth E; Biernacki, Diane; Maximos, Maryann; Kalavalapalli, Srilaxmi; Lomonaco, Romina; Suman, Amitabh; Cusi, Kenneth
Abstract : The underlying mechanisms responsible for the development and progression of non-alcoholic fatty liver disease (NAFLD) in patients with type 2 diabetes mellitus (T2DM) are unclear. Since the thyroid hormone regulates mitochondrial function in the liver, we designed this study in order to establish the association between plasma free T4 levels and hepatic triglyceride accumulation and histological severity of liver disease in patients with T2DM and NAFLD. This is a cross-sectional study including a total of 232 patients with T2DM. All patients underwent a liver MR spectroscopy ( 1 H-MRS) to quantify hepatic triglyceride content, and an oral glucose tolerance test to estimate insulin resistance. A liver biopsy was performed in patients with a diagnosis of NAFLD. Patients were divided into 5 groups according to plasma free T4 quintiles. We observed that decreasing free T4 levels were associated with an increasing prevalence of NAFLD (from 55% if free T4≥1.18 ng/dL to 80% if free T4<0.80 ng/dL, p=0.016), and higher hepatic triglyceride accumulation by 1 H-MRS (p<0.001). However, lower plasma free T4 levels were not significantly associated with more insulin resistance or more severe liver histology (ie, inflammation, ballooning, or fibrosis). Decreasing levels of plasma free T4 are associated with a higher prevalence of NAFLD and increasing levels of hepatic triglyceride content in patients with T2DM. These results suggest that thyroid hormone may play a role in the regulation of hepatic steatosis and support the notion that hypothyroidism may be associated with NAFLD. No NCT number required.